Creating Training Equipment and Kick Tests in Pencak Silat Using Internet of Things (IoT) Technology - Juli Candra; Faridatul A'la; Ali Mardius (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
The development of digital technology in the world of sports (sports science) demands objectivity in measuring athlete performance, including in the martial art of Pencak Silat. To date, evaluation of kick speed and power is often carried out conventionally or subjectively through coach observations, resulting in a lack of accurate athlete development data. This study aims to design and build an Internet of Things (IoT)-based kick training and testing system capable of measuring performance parameters in real time and accurately. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The developed hardware consists of a force sensor and an accelerometer integrated with an ESP32 microcontroller as the system's brain. Data captured by the sensor when the athlete kicks is sent wirelessly via a WiFi network to a cloud-based database. The information is then displayed in graphical and numerical form through a web dashboard application, including impact force variables (in Newtons) and reaction speed (in milliseconds). Test results show that this tool has a high level of precision with minimal error compared to standard measuring instruments. The implementation of IoT technology allows coaches to remotely monitor athletes' training progress and digitally track their performance. In conclusion, this IoT-based training and kick testing tool is effective as an objective evaluation tool, helping to improve training quality and supporting the digitalization of the Pencak Silat training system towards international achievement.